2014
DOI: 10.1242/jeb.100214
|View full text |Cite
|
Sign up to set email alerts
|

mRNA degradation: an underestimated factor on steady-state transcript levels of cytochromecoxidase subunits?

Abstract: Steady-state mRNA levels are determined by synthesis and degradation; however, changes in mRNA levels are usually attributed to transcription. For cytochrome c oxidase (COX), cold acclimation typically leads to an increase in COX activity while transcript levels for the nuclear-encoded subunits change non-stoichiometrically. Whether those patterns are caused by differences in subunit transcription rates, decay rates or both was not known. We assessed decay rates of transcripts for COX subunits, including repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
12
1
1
Order By: Relevance
“…Regulation of COX subunit transcription at the mRNA level has been explored in the context of temperature fluctuations in goldfish. It was concluded that individual subunits are universally controlled at the transcription level, but degradation rates may differ and be responsible for differential transcript levels in cold acclimation [128]. Recently, the mitochondrial ATPase lactation elevated 1 (LACE1) was investigated for its role in degradation of COX, based on sequence homology with the yeast ATPase Afg1, which serves a similar role [129, 130].…”
Section: Synthesis and Assembly Of Cytochrome C Oxidasementioning
confidence: 99%
“…Regulation of COX subunit transcription at the mRNA level has been explored in the context of temperature fluctuations in goldfish. It was concluded that individual subunits are universally controlled at the transcription level, but degradation rates may differ and be responsible for differential transcript levels in cold acclimation [128]. Recently, the mitochondrial ATPase lactation elevated 1 (LACE1) was investigated for its role in degradation of COX, based on sequence homology with the yeast ATPase Afg1, which serves a similar role [129, 130].…”
Section: Synthesis and Assembly Of Cytochrome C Oxidasementioning
confidence: 99%
“…This research extends these studies by focusing on the coldinduced increase in COX4-1 mRNA, which is attributed primarily to increases in the rate of transcription (Bremer and Moyes, 2014). Mammalian studies on muscle mitochondrial biogenesis have variously implicated many transcriptional regulators, including NRF-1, NRF-2, retinoic acid X receptor α, estrogen-related receptor α, thyroid receptor α and PPARs (Scarpulla, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…Under conditions that lead to a modest increase in COX activity, the mRNA for individual subunits may decline, remain unchanged, increase in parallel or increase many fold more than COX activity (Duggan et al, 2011). Furthermore, at least some of the increase in COX subunit mRNA can be attributed to decreases in mRNA degradation rather than simply increases in synthesis (Bremer and Moyes, 2014). The complex relationships between COX gene expression and COX activity epitomize the importance of considering both transcription and non-transcriptional mechanisms for adaptive remodelling of metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, our study highlights the importance of how transcriptome data is interpreted. While it is generally assumed that changes in steady-state mRNA levels stem from changes in the rate of transcription, varying the rate of degradation also changes steady-state levels; this phenomenon has been observed at both mRNA and protein levels in the cold acclimation of fish (Sidell, 1977;Bremer and Moyes, 2014). Recently, the balance between mRNA synthesis and degradation rates was examined on a global scale in cultured mammalian cells, demonstrating complex gene-specific effects of transcription, processing, decay, and translation (Rabani et al, 2011;Schwanhausser et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To balance the decreased transcription, mRNA degradation during torpor also must be reduced to maintain cellular integrity and permit function in early arousal. Just as with transcription, low body temperature (i.e., Q10 effects) will slow rates of RNA degradation (Burka, 1969;Bremer and Moyes, 2014), but it is unclear how these two opposing activities will converge after two weeks to determine the steady-state abundance of specific RNAs at the end of a torpor bout. While the general consensus is that the transcriptome is largely stable during torpor (reviewed by ), this view is based upon results (Frerichs et al, 1998;O'Hara et al, 1999;Knight et al, 2000;Williams et al, 2005) where ongoing degradation is not readily distinguishable from a stable transcriptome because of the sampling and normalization strategies employed.…”
Section: Introductionmentioning
confidence: 99%